Eustacjański kontekst doktryny o ubóstwie monastycznym w pismach ascetycznych św. Bazylego Wielkiego - Kasprzak, Dariusz (Vox Patrum, 2010)
We can distinguish two essential approaches to the issue of monastic poverty in the teaching of St Basil: a critical anti-Eustachian and a positive, unpolemical attitude. He pointed out his critical approach to main points of the doctrine introduced by Eustachius i.e.: the refusal of marriage and condemnation of the possession of any property, even in order to use it for charity purposes. It is clearly visible in his late writings – Letters, Moralia. St. Basile proved, in these writings, the necessity of the use of properties, from a biblical and ecclesiastical point of view because – for example to pay taxes. The positive approach which accepted voluntary poverty is clearly visible in his Moralia, Greater Asketikon and Lesser Asketikon. The bishop of Caesarea considered voluntary poverty as the mean to achieve a state of the unity of Christian life. The only Christian purpose is to give glory to the Lord and salvation.